Comparison of gut microbiota in male MAFLD patients with varying liver stiffness - Zhang, Yuheng; Yan, Su; Sheng, Shifeng; Qin, Qian; Chen, Jingfeng; Li, Weikang; Li, Tiantian; Gao, Xinxin; Wang, Lin; Ang, Li; Ding, Suying (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose. To investigate the correlation between the structure and function alterations of gut microbiota and biochemical indicators between persons with the case group (liver stiffness (LSM) ≥7.4 kPa) and control group (LSM＜7.4kPa). Methods. A total of 85 males with MAFLD, of which 17 males were in the case group and 68 males were matched in the control group were included. Waist circumference, blood pressure, and BMI were measured. The clinical parameters such as WBC, ALT, AST, GGT, ALB, TBIL, TC, TG, HDL, LDL, FPG, Cr, SUA, HbA1c, CAP and LSM were examined. Whole-genome shotgun sequencing technology and HUMAnN2 MetaCyc pathway database were used to detect the composition and pathways of the gut microbiota. Statistical analyses were performed using R program. Chi-square tests, Student’s t-test, wilcoxon rank sum test and the Mann-Whitney test were used. Results. Through whole-genome sequencing the gut microbes in the LSM≥7.4 kPa group were different from the control group. There were 7 kinds of bacteria that had different distributions in the two groups. Prevotella copri, Phascolarctobacterium succinatutens, Eubacterium biforme, and Collinsella aerofaciens increased in the case group(P<0.05). Bacteroides coprocola, Bacteroides stercoris and Clostridiales bacterium_1_7_47FAA decreased in the case group(P<0.05). Prevotella copri was significantly enriched in the case group. A total of 32 pathways were found to be significantly different between the two groups after removing low abundance pathways. Most pathways which were related to biosynthesis of amino acids, vitamins, nucleosides and nucleotides, etc. were enriched in the case group. Conclusion. The structure and function of the gut microbiota in the LSM ≥7.4 kPa group have altered. It may provide new ideas for the mechanism of liver fibrosis.